High closing - Joel Fried (The University of Western Ontario, Department of Economics, 2000)
Price manipulation in financial markets is a prohibited activity, but identifying it is a problem in thinly traded securities markets. One service that clients expect of a portfolio manager is to provide up-to-date valuations. Actions to obtain these valuations are regarded as proper by the Exchange and, in the past, have not been considered price manipulation, even though they may give that appearance. I argue that the evidence in the RT Capital high closing case suggests that it was attempting to obtain these valuations rather than manipulate prices against its clients' interests. In effect, the regulators have extended the definition of price manipulation to prohibit activities that are to the benefit of the small investor and market efficiency and cannot be justified on a cost/benefit basis.
Keywords: 330; Wertpapierhandel; Börsenkurs; Wucher; Prinzipal-Agent-Theorie